Examining the impact of artificial intelligence (AI) tools on Saudi Arabian ESL students’ writing skills - Abduljawad, Samah (Erudita: Journal of English Language Teaching, 2024)
The present study aims to determine the impact of the Artificial Intelligence (AI) tool on ESL students’ writing skills in Saudi Arabia. A mixed-method approach was designed in this study. A t-test approach was used for the quantitative research. The mean of the pre-test was 51.8, while the mean of the post-test was 79.46. The significant difference in the scores highlighted the positive influential effect of the AI tools on the ESL students’ writing skills. A focus group interview of five students was conducted for the qualitative analysis. The focus group participants discussed the following codes: AI’s impact on content organization, grammar, and vocabulary, as well as the strengths and weaknesses of the AI tools. The interview highlighted that AI tools benefited students’ learning by providing chances in writing patterns, their improvement, and their structures to show the flow of coherent patterns. There were also disparities in AI tool use, which included the possibility of coming up with content not being referred to as human-like, failure to recognize creativity, and capacity to cheat. This research can help future researchers and instructors explore how to use AI tools for writing effectively, enhancing the strengths and diminishing the possible weaknesses.